2016
DOI: 10.1016/j.applthermaleng.2016.07.046
|View full text |Cite
|
Sign up to set email alerts
|

Thermal energy storage using chloride salts and their eutectics

Abstract: Achieving the goals of the U.S. Department of Energy (DOE) Sunshot initiative requires 1) higher operating temperatures for concentrating solar power (CSP) plants to increase theoretical efficiency, and 2) effective thermal energy storage (TES) strategies to ensure dispatchability. Current inorganic salt-based TES systems in large-scale CSP plants generally employ molten nitrate salts for energy storage, but nitrate salts are limited in application to lower temperatures-generally, below 600°C. These materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(55 citation statements)
references
References 71 publications
1
47
0
Order By: Relevance
“…In the future, renewable energy must compete in the marketplace in the United States without incentives. The main advantage of concentrating solar power (CSP) is that thermal storage enables power generation to match demand better than photovoltaics or wind . The first generation of CSP did not use thermal storage and the second generation power tower CSP was deployed with nitrate salt thermal storage .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the future, renewable energy must compete in the marketplace in the United States without incentives. The main advantage of concentrating solar power (CSP) is that thermal storage enables power generation to match demand better than photovoltaics or wind . The first generation of CSP did not use thermal storage and the second generation power tower CSP was deployed with nitrate salt thermal storage .…”
Section: Introductionmentioning
confidence: 99%
“…To be competitive in future markets perhaps with utility‐scale battery storage options, the third generation of CSP is envisioned to have a >50% thermal efficiency by using a supercritical CO 2 power block operating at >700°C . While a variety of thermal storage concepts can be considered, one strategy is to select a salt with higher temperature capabilities, such as chloride or fluoride salts, with chloride salts being favored due to lower costs . However, numerous recent isothermal assessments have indicated that chloride salts can be extremely corrosive to structural alloys at ≥600°C .…”
Section: Introductionmentioning
confidence: 99%
“…60%NaNO 3 , 40%KNO 3 (solar salt) and 53%KNO 3 , 40%NaNO 2 , 7%NaNO 3 (Hitec) have become the two most commonly used molten salt media in CSP (Concentrating Solar Power) plants. 1,2 Compared with carbonate, 3,4 chloride salt, 5,6 uoride salt, 7,8 sulfate 9 or molten hydroxide, 10 nitrate 11-14 is the best heat storage and heat transfer medium with low viscosity, low saturated vapor pressure, low corrosivity, large specic heat and so on. However, the thermal conductivity of solar salt is only about 0.5 W (m K) À1 , 15 which may result in lower energy conversion efficiency and limit the utilization efficiency of solar energy.…”
Section: Introductionmentioning
confidence: 99%
“…It is extensively acknowledged that thermal energy storage (TES) has played the leading role in efficient utilization of renewable energy such as solar energy, geothermal and industrial waste heat [2]. TES technology is able to overcome the disadvantages of time discrepancy, distance discrepancy and instability of renewable energy by adjusting mismatch between energy supply and demand [3]. Generally speaking, TES can be divided into three aspects, i.e.…”
Section: Introductionmentioning
confidence: 99%